2023
DOI: 10.1097/md.0000000000035604
|View full text |Cite
|
Sign up to set email alerts
|

Role of TOP2A and CDC6 in liver cancer

Wei Jia,
Xiang Liu,
Zhilei Zhang

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors with high mortality worldwide, which is characterized by aggressive growth and metastasis. However, the relationship between TOP2A and CDC6 and HCC remains unclear. GSE121248 and GSE101728 profiles for liver cancer were downloaded from the gene expression omnibus database generated using GPL21047and GPL570. Differentially expressed genes (DEGs) were screened and weighted gene co-expression network analysis was performed. The construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…DNA topoisomerase 2-α (TOP2A) is an enzyme that can control and change the topological state of DNA in the process of transcription [32] . Many studies have shown that TOP2A can be used as a prognostic biomarker and potential therapeutic target for tumors such as Colorectal Cancer [33] , Cholangiocarcinoma [34] , breast cancer [35] .…”
Section: Discussionmentioning
confidence: 99%
“…DNA topoisomerase 2-α (TOP2A) is an enzyme that can control and change the topological state of DNA in the process of transcription [32] . Many studies have shown that TOP2A can be used as a prognostic biomarker and potential therapeutic target for tumors such as Colorectal Cancer [33] , Cholangiocarcinoma [34] , breast cancer [35] .…”
Section: Discussionmentioning
confidence: 99%